2017
DOI: 10.1080/08927014.2017.1322585
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial effect of hydrogen peroxide-titanium dioxide suspensions in the decontamination of rough titanium surfaces

Abstract: The chemical decontamination of infected dental implants is essential for the successful treatment of peri-implantitis. The aim of this study was to assess the antibacterial effect of a hydrogen peroxide-titanium dioxide (HO-TiO) suspension against Staphylococcus epidermidis biofilms. Titanium (Ti) coins were inoculated with a bioluminescent S. epidermidis strain for 8 h and subsequently exposed to HO with and without TiO nanoparticles or chlorhexidine (CHX). Bacterial regrowth, bacterial load and viability af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 56 publications
1
26
0
Order By: Relevance
“…The number of viable bacteria, as determined by the number of colony-forming units (CFUs), can be linearly correlated with the detected luminescence until bacteria growth reaches the stationary phase (Figure 13 A). 170 After that, luminescence could no longer be correlated with the number of cells, and the observed decrease in luminescence could not be related to the death of bacteria, but rather to decreased metabolic activity due to the lack of nutrients and oxygen in the sealed well plates. 171 In Figure 13 B, representative luminescence profiles for normal bacterial growth (in presence of a polarized titanium disc) and for inhibited bacterial growth (in presence of a doxycycline coated disc) are shown.…”
Section: Bacteria Studymentioning
confidence: 98%
“…The number of viable bacteria, as determined by the number of colony-forming units (CFUs), can be linearly correlated with the detected luminescence until bacteria growth reaches the stationary phase (Figure 13 A). 170 After that, luminescence could no longer be correlated with the number of cells, and the observed decrease in luminescence could not be related to the death of bacteria, but rather to decreased metabolic activity due to the lack of nutrients and oxygen in the sealed well plates. 171 In Figure 13 B, representative luminescence profiles for normal bacterial growth (in presence of a polarized titanium disc) and for inhibited bacterial growth (in presence of a doxycycline coated disc) are shown.…”
Section: Bacteria Studymentioning
confidence: 98%
“…The radicals formed are highly oxidative and essential for the high antibacterial activity found in TiO2-H2O2 suspensions. 36 Since anatase has been suggested to be the more active phase in the catalytic decomposition of H2O2 on TiO2 compared to rutile, 26 the aim of the applied surface modification was to deposit a thin anatase layer onto the underlying rutile surface of the prepared porous TiO2 substrates. The rutile phase of the used TiO2 scaffolds used in this study is an inevitable consequence of the high sintering temperatures required to achieve adequate mechanical strength needed in load bearing applications.…”
Section: Coating Characteristicsmentioning
confidence: 99%
“…The ability to form such biofilms on various substrates in a monoculture in vitro has made S. for the metabolic activity 35 and viability 36 during the colonisation of the modified TiO2 surfaces. The results of the in vitro assays demonstrate that TiO2 sol-gel coatings show antibacterial activity against S. epidermidis after the treatment with H2O2.…”
Section: Antibacterial Activitymentioning
confidence: 99%
“…However when adding small amounts of H 2 O 2 , rutile has been shown to increase hydroxyl radical formation under light irradiation [ 16 18 ]. H 2 O 2 is in itself an effective antiseptic and with a concentration of 3 vol.% (950 mM) has been shown to be an effective treatment against S. epidermidis biofilms on titanium dental implant surfaces in vitro [ 19 21 ]. TiO 2 in combination with H 2 O 2 has been shown to give rise to an increased synergistic bactericidal effect [ 19 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…H 2 O 2 is in itself an effective antiseptic and with a concentration of 3 vol.% (950 mM) has been shown to be an effective treatment against S. epidermidis biofilms on titanium dental implant surfaces in vitro [ 19 21 ]. TiO 2 in combination with H 2 O 2 has been shown to give rise to an increased synergistic bactericidal effect [ 19 , 21 ]. Studies have shown that small amounts of H 2 O 2 together with TiO 2 of the allotropic form rutile under light exposure is the most effective combination to degrade the organic dye Rhodamine B [ 22 ], as well as inactivate the multiresistant bacterium Klebsiella pneumoniae [ 23 ].…”
Section: Introductionmentioning
confidence: 99%